Waqf in Johor: A Systematic Literature Review of Governance, Legal Framework, Economic Sustainability, and Development - Baharudin, Mohammad Hidir; Mohd Yusoff, Rahmawati (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
Background: Waqf has significantly supported Malaysian society, including Johor, primarily contributing to religious, educational, and social institutions. Recently, increased attention has been paid to innovations and challenges within Johor’s waqf sector. Purpose: This review examines waqf research in Johor over the past decade, focusing on governance, legal frameworks, economic sustainability, historical background, development, and recent advancements in waqf. Methodology: Keywords related to waqf and Johor were employed to examine numerous academic journals, conference proceedings, policy papers, and reputable reports from 2013 to 2025. Ongoing studies examining waqf in Johor or utilising Johor as a case study were included, while works covering the subject broadly without specific reference to Johor were excluded. Relevant sources were thematically analysed. Key Findings: Waqf affairs in Johor reflect the conservative designs of the State Islamic Religious Council (SIRC) alongside the bold strategies of corporate waqf. Current waqf laws in Johor derive from state regulations, although certain areas remain questionable and require updates. Johor has made significant economic strides by implementing innovative management of trust assets, issuing waqf shares, and garnering substantial public donations for waqf purposes. Nevertheless, issues like underdeveloped assets, insufficient resources, and data challenges persist. Implications: In conclusion, while Johor is viewed as a model for waqf, it faces various challenges related to laws and operations, similar to those faced by many other states. Enhancing governance, modernising the legal framework, improving effective management, and fostering public awareness are critical for maximising the impact of waqf in Johor. Conclusion: Innovations in waqf in Johor illustrate the ability to adapt to changes while maintaining effective oversight. Future research should investigate the long-term social impact of Johor’s waqf activities, with a focus on the necessary steps for legal reforms, training, and effective asset management in waqf.